Follicular occlusion triad - Yugal Kishore Sharma; Shivanti Chauhan; Kirti Deo (Wolters Kluwer Medknow Publications, 2018)
Follicular occlusion triad is a complex comprising three conditions - hidradenitis suppurativa (HS), acne conglobata, and dissecting cellulitis of the scalp - which share the same underlying pathological process of follicular occlusion. Although these constituents are frequently occurring conditions, the triad per se is not commonly reported. We report the case of a 32-year-old male with Hurley Stage II HS, acne conglobata, and dissecting cellulitis of the scalp with mild anemia (hemoglobin: 10.2 g/dL) and raised C-reactive proteins (15 mg/dL). To the best of our knowledge, this appears to be the third case of follicular occlusion triad from India; also probably, only one case has earlier been reported from India with the additional condition of pilonidal cyst, i.e., a follicular occlusion tetrad.